Análise de investimento em confinamento bovino no centro-oeste brasileiro: um estudo de caso. - Lopes Santos, David Ferreira [UNESP] (2013)
This study analyzed the economic viability of an investment in feedlot cattle on a farm in the midsize state of Goias. The research identified that different thematic studies whose interests have focused mainly on cost analysis and profitability punctual. Differently, this study used the approaches of the Discounted Cash Flow (DCF) and the Real Options Theory (ROT). The first used the projected cash flow for 10 years and a discount rate determined by CAPM at 8% p.a. for containment of heads 400. The second was modeled by the binomial model of Cox, Ross and Rubinstein (1979) incorporating the option of waiting. This methodology has not been employed in Brazilian cattle industry. The search results pointed to the economic viability of the project when considered possible scenarios for the different price ranges of the ox that state bushel. In addition, the TOR proved to be a more robust tool for investment analysis, by incorporating the flexibility of farmers to wait for the right time to make the confinement.